Determinants of Adapted Behaviors on Employee and Entrepreneurs Against the Covid-19 Pandemic: Theory of Planned Behavior - M. Azka Kesuma Wardana; Eko Ruddy Cahyadi; Alim Setiawan Slamet (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
New Normal is a change in behavior to continue carrying out normal activities but coupled with the implementation of health protocols to prevent Covid-19 transmission. In Indonesia itself, the new normal is applied as a realistic response from the Indonesian government to the existence of COVID-19 as well as the results of the analysis in various sectors of national life, especially the future of the national economy in the medium and long term. After the implementation of the new normal, it automatically affects the routine activities carried out by the community, especially those activities that were restricted by the government at the time of the New Normal. This study aims to analyze the factors that influence behavior change after the application of the New Normal in the Covid-19 Pandemic. A modified Theory of Planned Behavior is used in this study using testing through Structural Equation Modeling (SEM-PLS). A total of 427 respondents who have worked have answered the online questionnaire containing 61 questions. The results of this study indicate that knowledge and understanding of covid-19 make people understand the severity they feel and the vulnerabilities they may experience. The severity and vulnerability they feel also have an influence on their attitudes, behavior control, past behavior, and subjective norms so that they have a strong factor in building their intention to behave during the pandemic when the new normal is enacted. The intention that has been built with the support of attitudinal factors, past behavior, subjective norms, and behavior control also changes people's behavior. Employees are able to more moderate the relationship between attitudes towards intention and the relationship between past behavior and intention than entrepreneurs.